National Curriculum for Physical Education in the United States. Issue 2 (3rd April 2017) - Oh, Junghwan; Graber, Kim C.
ABSTRACT: Since the publication of A Nation at Risk, some scholars have argued that a national curriculum and national testing are necessary to hold school personnel accountable for student achievement and, ultimately, to raise educational standards. The idea of developing a nationwide curriculum has been widely debated in the United States, where the traditions of local control and state responsibility are dominant. Thus, this article examines the relevance and feasibility of a uniform curriculum in physical education. A core curriculum for physical education has the potential to provide clear goals, coherent instructional guidelines, and relevant assessments aligned with designated program outcomes. A more advanced curricula framework with clear guidance for P-12 curricula and pedagogical practices could promote system-wide changes in school-based physical education. In contrast, the adoption of an overly rigid national curriculum would create a stifling educational context where cultural differences and local flexibility are not allowed.